2011
DOI: 10.1371/journal.pone.0019121
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Chemotherapy of Rat Glioblastoma Using Doxorubicin-Loaded PLGA Nanoparticles with Different Stabilizers

Abstract: BackgroundChemotherapy of glioblastoma is largely ineffective as the blood-brain barrier (BBB) prevents entry of most anticancer agents into the brain. For an efficient treatment of glioblastomas it is necessary to deliver anti-cancer drugs across the intact BBB. Poly(lactic-co-glycolic acid) (PLGA) nanoparticles coated with poloxamer 188 hold great promise as drug carriers for brain delivery after their intravenous injection. In the present study the anti-tumour efficacy of the surfactant-coated doxorubicin-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(83 citation statements)
references
References 25 publications
3
74
0
5
Order By: Relevance
“…35 Similarly, we also observed high EE of DOX (90%), which might be related to the conversion of DOX hydrochloride into a less soluble free base to facilitate DOX distribution into the oil phase. 36 A slightly improved EE of DOX with the increase of Cur was detected, indicating a promoting effect of Cur on the encapsulation of DOX. This result verified the hypothesis in terms of the zeta potential measurement.…”
Section: Physical Characterization Of Dox/ Cur-npsmentioning
confidence: 87%
“…35 Similarly, we also observed high EE of DOX (90%), which might be related to the conversion of DOX hydrochloride into a less soluble free base to facilitate DOX distribution into the oil phase. 36 A slightly improved EE of DOX with the increase of Cur was detected, indicating a promoting effect of Cur on the encapsulation of DOX. This result verified the hypothesis in terms of the zeta potential measurement.…”
Section: Physical Characterization Of Dox/ Cur-npsmentioning
confidence: 87%
“…anti-tumor efficacy in a glioblastoma rat model [453]. The modifications proposed by these authors were the stabilization by polyvinylalcohol (PVA) and human serum albumin (HAS), and the inclusion of lecithin in the core of the PLGA/HSA formulations that stabilize the coating of poloxamer 188 due to the affinity between both components.…”
Section: Wohlfart Et Al and Tested By Histological And Immunohistochmentioning
confidence: 99%
“…The modifications proposed by these authors were the stabilization by polyvinylalcohol (PVA) and human serum albumin (HAS), and the inclusion of lecithin in the core of the PLGA/HSA formulations that stabilize the coating of poloxamer 188 due to the affinity between both components. Studies on a rat glioblastoma model demonstrated the enhanced anti-tumor effect of the doxorubicin-loaded lecithincontaining PLGA/HSA formulation coated with poloxamer 188, the key ingredient for the delivery of the drug to the brain [453].…”
Section: Wohlfart Et Al and Tested By Histological And Immunohistochmentioning
confidence: 99%
“…3,6 Different anticancer drugs, including Tamoxifen citrate, were loaded in the PLGA nanoparticles by many researchers. [7][8][9][10] Tamoxifen citrate, an antiestrogenic compound, is the first choice for hormonal treatment of breast cancer in both post and premenopausal women for the last few decades. It is often used as an adjuvant therapy following primary treatment of early stage breast cancer.…”
Section: Introductionmentioning
confidence: 99%